2017
DOI: 10.1002/cjoc.201600800
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Magnetic Microsphere‐Gold Nanoparticle‐Immobilized Enzyme Batch Reactor and Its Application to Enzyme Inhibitor Screening in Natural Extracts by Capillary Electrophoresis

Abstract: A novel strategy for screening the enzyme inhibitors from the natural products by capillary electrophoresis (CE) with a pre column enzyme batch reactor prepared by magnetic microsphere (MB)-gold nanoparticles (AuNPs) is reported. The enzyme batch reactor was prepared by immobilizing the enzymes on the MB conjugated AuNPs (MB-AuNPs). To demonstrate this strategy, xanthine oxidase (XOD) was employed as a model for the activity of the enzyme, inhibition study, and inhibitor screening. With the developed CE method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This approach not only realized rapid separation of enzymes from the reaction mixture by magnetism, but also can improve the stability of enzymes. Similar study was also reported, XOD was immobilized on magnetic microsphere ‐gold NPs (AuNPs) for evaluating the XOD inhibitory effects of extracts from Cortex Phellodendri and Rhizoma Galangae .…”
Section: Applicationssupporting
confidence: 66%
See 1 more Smart Citation
“…This approach not only realized rapid separation of enzymes from the reaction mixture by magnetism, but also can improve the stability of enzymes. Similar study was also reported, XOD was immobilized on magnetic microsphere ‐gold NPs (AuNPs) for evaluating the XOD inhibitory effects of extracts from Cortex Phellodendri and Rhizoma Galangae .…”
Section: Applicationssupporting
confidence: 66%
“…CE in screening of bioactive compounds derived from natural products from 2007 to 2017 was well reviewed by Ma et al . Herein, we would only focus on the recent applications of CE in the screening of enzyme or receptor inhibitors, such as tyrosinase (TYR) inhibitors , protein kinase inhibitors (PKIs) of protein kinase A (PKA) , neuraminidase inhibitors , mammalian target of rapamycin (mTOR) inhibitors , epidermal growth factor receptor (EGFR) inhibitors , α‐glucosidase inhibitors , xanthine oxidase (XOD) inhibitors , histone deacetylase 1 (HDAC1) inhibitors , break point cluster region Abelson tyrosine kinase (BCR‐ABL) inhibitors , and thrombin (THR) inhibitors .…”
Section: Applicationsmentioning
confidence: 99%
“…This was shown by Liu et al for lipase [55] and Wang et al on separate studies. The latter group grafted xanthine oxidase onto magnetic microspheregold nanoparticles [83].…”
Section: Magnetic Microreactorsmentioning
confidence: 99%
“…The developed method has been employed to screen α‐Glu inhibitors from 18 TCMs. Based on magnetic microsphere (MB)‐gold nanoparticles (AuNPs), xanthine oxidase (XOD) was immobilized and used for screening XOD inhibitors from the natural products . With the proposed method, the screening of two natural extracts from Cortex phellodendri and Rhizoma galangae was taken and the results indicated its positive effect for XOD inhibition.…”
Section: Off‐line Screening Of Enzyme Inhibitorsmentioning
confidence: 99%